Comparative study of landslide cases in Malaysia: lesson learnt - Abang Hasbollah, Dayang Zulaika; Bong, Shi May; Romanah, Nurul Amaniyah; Mohd Taib, Aizat; Ramli, Ahmad Bukhari; Abd Rahman, Norinah; Mat Sait, Khairun Nissa; Jusoh, Siti Norafida (Books & Journals Private Ltd., 2021)
Landslide events have the devastating impacts on human lives, damage to the physical asset (building, roads and highways), broken of utility supply lines and loss of environmental resources and economic costs. In the period of 59 years from 1961 to 2019, Malaysia has recorded 91 distinct landslide events which caused 721 deaths. Urbanization and the high rate of population growth accelerate the construction of flat ground. In order to cater to this demand, land utilization becomes more important and generally shifts toward the hilly area or expands underground. This paper presents the comparative studies between 4 landslide cases to come out with the most common causal factors and rehabilitation methods taken. Studies showed that landslides occurred in Malaysia is mainly due to the intense and prolonged rainfall event. Since Malaysia is experiencing tropical weather, frequent and intense rainfall event is unavoidable. Therefore, the impact of rainfall shall be considered and included in the design to minimize the risk of landslide. Besides, human factors such as deforestation, design error and construction error should also be reviewed to effectively prevent the occurrence of the landslide.